KEPUASAN WISATAWAN TENTANG DAYA TARIK WISATA DI OBJEK WISATA PANTAI GANDORIAH PARIAMAN - Utami, Nidya Lovitha; Waryono, Waryono; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research purpose to know how satisfied the tourist about tourist attractionin Gandoriah Beach Pariaman which include three of tourism satisfiedindicators that are the fulfillment of tourist experctations, the desire to useproducts/services again, and the desire to promote products/services to others.This type of research is descriptive research using survey method. Populasi inthis research amounted to 222.884 people’s and for sample this researchamounted 100 people’s. Sampling technique is non probality sampling usingincidental sampling. Data collection using a questionnaire that tested forvalidity and realibility. Based on the result of the research shown that touristsatisfaction about tourism attraction of Pantai Gandoriah Pariaman tourism isfairly satisfy categorized with avarege value 94,41 at the range score 83-103with 44% percentage.Keyword: satisfied, tourist, tourist attraction, Gandoriah Beach Pariaman